G14 The use of pyloric EndoFLIP to assess response to botulinum toxin injection in children. (12th September 2022) - Popescu, Mara; Kammermeier, Jochen; Vora, Rakesh; Mutalib, Mohamed
Abstract : Background: Gastrointestinal complaints are common in children with neurodisabilities, vomiting, retching and poor feed tolerance are frequently reported. EndoFLIP is used to assess compliance and distensibility of the pylorus and can predict response to Botulinum Toxin in adult with gastroparesis. We aimed to review pyloric muscle measurements using EndoFLIP via existing gastrostomy stoma in children with neuromuscular disabilities and significant foregut symptoms and assess response to intrapyloric Botulinum Toxin by using modified Gastroparesis Cardinal Symptom Index (GCSI). Methods: Retrospective review of clinical notes of all children who underwent pyloric EndoFLIP assessment in Evelina London Children Hospital from March 2019 to June 2021. EndoFLIP catheter was inserted at the time of endoscopy via existing gastrostomy tract. Results: Eighteen measurement in 10 children were obtained, mean age 10.7 ± (4.2) years. Measurements (pre and post Botox) were obtained with 20, 30 and 40mls balloon volume. Diameter (6.4, 6.6), (8.1, 8.4) and (10.6, 9.9), compliance (99.8, 137.5), (88.5, 143.7) and (107.1, 96.1) mm3/mmHg, distensibility (2.9, 3.5), (3.2, 3.2) and (3.0, 3.1) mm2/mmHg and balloon pressure was (13.4, 10.8), (18.7, 9) and (10.6, 9.9) mmHg. 8 children improved clinically as measured by GCSI and EndoFLIP measurements after Botulinum Toxin injection. Conclusions: In children with neurodisabilities who present with symptoms suggestive of poor gastric emptying do have a low pyloric distensibility and poor compliance. EndoFLIP via existing gastrostomy tube is quick and easy to perform. Intrapyloric Botulinum Toxin appear to be safe and effective in this cohort of children leading to clinical and measurements improvement.